Development of a digital tool to assist in monitoring compliance for a public health initiative: “A Better Choice Food and Drink Supply Strategy for Queensland Healthcare Facilities” - Hai Pham; Sherridan Cluff; Mathew Dick; Erica Clifford; Nicole McDonald; Jason D. Pole (PLoS ONE, 2026)
Background Health and Wellbeing Queensland (Australia) is leading Queensland Government efforts to enhance food environments, ensuring that Queenslanders have access to healthy food and drinks options in places outside their homes. In healthcare settings, the A Better Choice (ABC): Food and Drink Supply Strategy for Queensland Healthcare Facilities is a policy that sets targets for the availability and promotion of food and drinks in retail outlets and vending machines with the aim of providing and promoting healthier options for staff and visitors. To strengthen policy action, a mandatory Health Service Directive: Healthier food and drinks at healthcare facilities (Directive) requires Hospital and Health Services (HHS) to meet ABC targets. Compliance with the Directive is assessed through annual audits. Objective The objective of this study was to establish an enduring data and analytics solution to assist in the implementation of ABC and monitoring of compliance with the Directive. Methods The Queensland Digital Health Centre, in collaboration with Health and Wellbeing Queensland developed a digital dashboard to report and manage audit data on food and drinks supplied in retail outlets and vending machines across Queensland public HHSs. Annual survey data was completed by 16 HHSs and Mater Health. These data were checked, aggregated and loaded into the digital analytics dashboard. Results The development process resulted in a replicable digital dashboard for reporting and decision-making. The ABC dashboard provides previous and current compliance data for all HHSs, featuring visualisations that illustrate changes in compliance over time to help identify emerging trends. Users can interact with the dashboard to filter data by HHS, year and by outlet and food or drink type. This digital innovation has facilitated faster delivery of food and drink supply trend analysis and compliance reporting for HHSs and statewide policy makers. Conclusions Digital dashboards for public health policy compliance enable greater interrogation of data and provide visualisation tools to track trends in compliance over time. This allows more responsive and effective action to increase the impact of public health policies.